La Ley Juárez - González Navarro, Moisés (El Colegio de México, A.C., 2006)
Benito Juarez, when recently appointed Minister  of Justice, decreed  on November 23rd,  1855,  the  so-called  “Ley  Juárez”, which  gave  place  to many  opinions in  favor and  against  it. Opinions against the  law  arose originally  in  affected  sectors—the Church, the Army,  and the Supreme Court of Justice—, for it had three essential points of political importance:  the supression  of privileges,  the  organization of the  Supreme  Court, and the creation of the Tribunal Superior del Distrito Federal (Superior Court of the Federal District). The controversy went far beyond its time, for it included, on the one hand, a strong discussion within the old political class and the press of the time, and on the other,  opinions from much later scholars, both followers and detractors.